Crop ontology: integration of standard variables - Valette, L.; Pietragalla, J.; Laporte, Marie-Angélique; Afolabi, A.; Boukar, O.; Cannon, Steven B.; Diers, D.W.; Dreher, K.A.; Gaur, Pooran M.; Guerrero, Alberto F.; Hash, C.T.; Hualla, V.; et al. (2016)
The Crop Ontology (CO, http://www.cropontology.org/) is a resource of the Integrated Breeding Platform (IBP, http://integratedbreeding.net/) providing breeders with crop specific terms for fieldbook edition and data annotation. Until Mai 2015, a plant phenotype was annotated with 3 CO identifiers for the trait, the method and the scale, respectively. Yet, breeders’ fieldbook and most phenotypic databases are designed to annotate a datapoint with only one identifier. To meet the need of providing one single identifier to an observation variable, the CO and IBP teams have worked on integrating the notion of variable into the CO. This has led to a thorough revision of the structure of the Trait Dictionary (TD) template. The TD template is a user-friendly xls file that is used to submit terms to CO which are then stored in the IBP Breeding Management System and other information systems (NextGen, Agtrials…).